COMPARATIVE ANALYSIS OF CHEMICAL COMPOSITION AND SPECTRAL PROPERTIES OF BIOCHAR PRODUCED FROM PIGEONPEA AND COTTON RESIDUES - K.C. NATARAJA*, D. BALAGURAVAIAH, CH. SRINIVASA RAO, T. GIRIDHARA KRISHNA, Y. REDDI RAMU; P. LAVANYA KUMARI (The Journal of Research ANGRAU, 2021)
The study was conducted during 2018-19 to characterize the biochar. Biochar from two different agricultural crop residues viz., pigeonpea (Cajanas cajan (L.) Millsp.) and cotton (Gossypium spp) were produced under the slow pyrolysis process and studied for their physico-chemical properties, carbon stability, recovery and spectral properties. The proximate analysis of biochars recorded higher biochar yield (24.5%), higher fixed carbon (63.84%), lower volatile matter (5.85%) and ash (16.2%) in pigeonpea compared to cotton biochar (yield 22.6%; fixed carbon 62.69%; volatile matter 6.90%; and ash 18.5%). The pH of biochar from pigeonpea and cotton was 9.86 and 9.82, respectively. Electrical conductivity (EC) values of biochar from pigeonpea and cotton are 2.04 and 2.53 dS m-1, respectively. The nutrient concentration of derived biochar indicates enrichment of carbon and depletion of nitrogen and other nutrient elements after slow pyrolysis process. The pigeonpea biochar had lower bulk density (0.26 g cm-3) compared to cotton biochar (0.29 g cm-3). The CEC of pigeonpea and cotton biochar is 44.33 and 33.86 cmol (P+) kg-1, respectively; the carbon recovery level after conversion of the pigeonpea and cotton residues to biochar was 27.6 and 29.0 %, respectively. The typical honey-comb like structure of pigeonpea biochar analysed through SEM micrographs revealed the relatively porous nature of pigeonpea biochar. The study demonstrates that both pigeonpea and cotton biochars are substantially different despite being produced under the same slow pyrolysis process.